Psychological distress and coping strategies among Indonesian psychologists during the COVID-19 pandemic: a two-wave cross-lagged study - Fitri Ariyanti Abidin; Ahmad Gimmy Prathama; Efi Fitriana; Evy Sulfiani Komala; Joeri K. Tijdink (Health Psychology and Behavioral Medicine)
Background: Psychologists play a crucial role in providing essential psychological aid to individuals navigating the challenges posed by the COVID-19 pandemic. However, studies focusing on the mental health of psychologists during the COVID-19 pandemic remain scarce. This study investigates the interaction between coping strategies and psychological distress among a group of Indonesian psychologists.Methods: This longitudinal study was conducted over two-time points in 2021, with data collected from April 29 to June 23 and again from September 1 to October 23. A total of ninety-seven psychologists, predominantly female (91 out of 97), participated. The data was collected through an online survey, where participants completed the Indonesian version of the Depression, Anxiety, and Stress Scale-21 (DASS-21) and the Brief COPE questionnaire. Multiple regression analysis was used to perform cross-lag analyses on the data.Results: The findings revealed that adaptive coping strategies were strong predictors of continued use of adaptive coping strategies six months later, while existing psychological distress strongly predicted future distress. Notably, maladaptive coping strategies demonstrated a similar pattern, predicting the continued use of maladaptive coping techniques over time, but they were also consistently associated with psychological distress across both time points, though they did not significantly predict future psychological distress.Discussion: These findings shed light on the dynamic nature of coping strategies and psychological distress among psychologists, presenting significant implications for their support systems and mental health during the challenges posed by the pandemic. Future studies should focus on how psychologists can reduce maladaptive coping strategies to be better equipped to handle very stressful situations such as a pandemic. Additionally, researchers should explore effective interventions and programs that can be implemented to enhance adaptive coping mechanisms, ultimately improving overall psychological resilience and well-being during crises.